Cellular Organelles Reorganization During Zika Virus Infection of Human Cells - García, Cybele C.; Vázquez, Cecilia A.; Giovannoni, Federico; Russo, Constanza A.; Cordo, Sandra M.; Alaimo, Agustina; Damonte, Elsa B. (Frontiers in Microbiology, 2020)
Zika virus (ZIKV) is an enveloped positive stranded RNA virus belonging to the genus Flavivirus in the family Flaviviridae that emerged in recent decades causing pandemic outbreaks of human infections occasionally associated with severe neurological disorders in adults and newborns. The intracellular steps of flavivirus multiplication are associated to cellular membranes and their bound organelles leading to an extensive host cell reorganization. Importantly, the association of organelle dysfunction with diseases caused by several human viruses has been widely reported in recent studies. With the aim to increase the knowledge about the impact of ZIKV infection on the host cell functions, the present study was focused on the evaluation of the reorganization of three cell components, promyelocytic leukemia nuclear bodies (PML-NBs), mitochondria and lipid droplets (LDs). Relevant human cell lines including neural progenitor cells (NPCs), hepatic Huh-7 and retinal pigment epithelial (RPE) cells were infected with the Argentina INEVH116141 ZIKV strain and the organelle alterations were studied by using fluorescent cell imaging analysis. Our results have shown that these three organelles are targeted and structurally modified during ZIKV infection. Considering the nuclear reorganization, the analysis by confocal microscopy of infected cells showed a significantly reduced number of PML-NBs in comparison to uninfected cells. Moreover, a mitochondrial morphodynamic perturbation with an increased fragmentation and the loss of mitochondrial membrane potential was observed in ZIKV infected RPE cells. Regarding lipid structures, a decrease in the number and volume of LDs was observed in ZIKV infected cells. Given the involvement of these organelles in host defense processes, the reported perturbations may be related to enhanced virus replication through protection from innate immunity. The understanding of the cellular remodeling will enable the design of new host-targeted antiviral strategies.